2017
DOI: 10.18632/oncotarget.18583
|View full text |Cite
|
Sign up to set email alerts
|

Combined BRD4 and CDK9 inhibition as a new therapeutic approach in malignant rhabdoid tumors

Abstract: Rhabdoid tumors are caused by the deletion of SMARCB1, whose protein encodes the SMARCB1 subunit of the chromatin remodeling complex SWI/SNF that is involved in global chromatin organization and gene expression control. Simultaneously inhibiting the main players involved in the deregulated transcription machinery is a promising option for preventing exaggerated tumor cell proliferation and survival as it may bypass compensatory mechanisms. In support of this hypothesis, we report efficient impairment of cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 53 publications
2
30
1
Order By: Relevance
“…Immunoblots of lysates from the spleens of MLL-2-engrafted mice showed that all treatments resulted in depletion of MYC and BCL2 (supplemental Figure 3) as in previous reports. 18 Consistent with on-target activity of CDKI-73, we observed reduced RNAPII-Ser2 phosphorylation with the single treatment (29%), which was further reduced (49%) in the combination. Most strikingly, combination treatment resulted in further reduction of the antiapoptotic protein MCL1, and increased levels of cleaved caspase 3, compared with either single agent alone, consistent with increased cell killing.…”
Section: Resultssupporting
confidence: 76%
“…Immunoblots of lysates from the spleens of MLL-2-engrafted mice showed that all treatments resulted in depletion of MYC and BCL2 (supplemental Figure 3) as in previous reports. 18 Consistent with on-target activity of CDKI-73, we observed reduced RNAPII-Ser2 phosphorylation with the single treatment (29%), which was further reduced (49%) in the combination. Most strikingly, combination treatment resulted in further reduction of the antiapoptotic protein MCL1, and increased levels of cleaved caspase 3, compared with either single agent alone, consistent with increased cell killing.…”
Section: Resultssupporting
confidence: 76%
“…These data suggest that BET inhibition by JQ1 can suppress MYC expression and activity in ATRT cells and significantly restrict cell growth, consistent with a recent report by Moreno et al who demonstrated a synergy between BRD4 and CDK9 inhibition in ATRT cells. 22 Interestingly, our data on BT16 cell responsiveness diverge from that of Trochia et al who showed relative resistance of BT 16 to JQ1 by MTS assay. 7 These differences could be due to measuring of long term growth compared to the short-term assay performed by Torchia et al 7 To determine whether the anti-tumorigenic capacity of BET-mediated MYC inhibition is extended to primary human tumors, we obtained cells from an ATRT patient biopsy and tested the impact of JQ1 in a short-term culture (MAF-794).…”
Section: Myc Inactivation By Chemical Inhibition Of Bet Proteins Suppcontrasting
confidence: 85%
“…These data suggest that BET inhibition by JQ1 can suppress MYC expression and activity in ATRT cells and significantly restrict cell growth, consistent with a recent report by Moreno et al . who demonstrated a synergy between BRD4 and CDK9 inhibition in ATRT cells . Interestingly, our data on BT16 cell responsiveness diverge from that of Trochia et al who showed relative resistance of BT 16 to JQ1 by MTS assay .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rational combination therapies are likely to greatly extend the therapeutic applications of selective inhibitors of tCDKs. Mechanistic studies and synthetic lethality screens have already numerous revealed pathways, other targeted agents, or conventional chemotherapeutics that can synergize with tCDK inhibitors [58,116,140,[144][145][146][147], and additional examples are likely to exist.…”
Section: Emerging Themesmentioning
confidence: 99%